Immortalized Adult Rodent Schwann Cells as In Vitro Models to Study Diabetic Neuropathy. (13th June 2011) - Sango, Kazunori; Yanagisawa, Hiroko; Takaku, Shizuka; Kawakami, Emiko; Watabe, Kazuhiko
Abstract : We have established spontaneously immortalized Schwann cell lines from normal adult mice and rats and murine disease models. One of the normal mouse cell lines, IMS32, possesses some biological properties of mature Schwann cells and high proliferative activities. The IMS32 cells under hyperglycemic and/or hyperlipidemic conditions have been utilized to investigate the pathogenesis of diabetic neuropathy, especially the polyol pathway hyperactivity, glycation, increased oxidative stress, and reduced synthesis of neurotrophic factors. In addition to the mouse cell lines, our current study focuses on the characterization of a normal rat cell line, IFRS1, under normal and high glucose conditions. These Schwann cell lines can be valuable tools for exploring the detailed mechanisms leading to diabetic neuropathy and novel therapeutic approaches against that condition.